Establishing Host Pathogen Relationship between Arachis hypogea and Cercospora arachidicola S. Hori by RAPD (Random Amplified Polymorphic DNA) Markers - R.C. Sharma2, Remya Mohanraj1* (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: RAPD (Random amplified polymorphic DNA) analysis was performed to establish host-pathogen relationship between Arachis hypogea and Cercospora arachidicola. The relationship between the host and pathogen was analyzed based on the dendrogram of RAPD patterns using UPGMA (Unweighed Pair GroupMethod with Arithmetic Mean). RAPD analysis in our study showed that there is a clear host pathogen relationship between Arachis hypogea and Cercospora arachidicola. Â  Key words: RAPD, Host- pathogen interaction, Arachis hypogea, Cercospora arachidicola Abbreviations: RFLP- Restriction fragment length polymorphism, PCR- polymerase chain Reaction, c-DNA- Complementary DNA